2003
DOI: 10.1063/1.1575736
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution electronic spectroscopy of a nonlinear carbon chain radical C6H4+

Abstract: A high-resolution gas-phase spectrum of a molecular absorption band around 604 nm is assigned as due to an electronic transition of a nonlinear C 6 H 4 ϩ planar species starting from its 2 AЉ electronic ground state. The spectrum is observed in direct absorption by cavity ringdown spectroscopy through a supersonic planar discharge through a mixture of acetylene in helium. The spectrum has a clear rotational and K-type structure. This allows an accurate determination of the B and C rotational constants and an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 26 publications
(24 reference statements)
1
35
0
Order By: Relevance
“…Besides the poly-acetylene progression HC n H + , with n as high as 8, a number of other carbon chain cations-for example, species of the series C 2n H 4 + are found. Such radicals are currently under research in spectroscopic studies; C 6 H 4 + , for example, was just recently shown to have a non-linear non-cyclic ground state structure [12].…”
Section: Mass Spectrometric Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the poly-acetylene progression HC n H + , with n as high as 8, a number of other carbon chain cations-for example, species of the series C 2n H 4 + are found. Such radicals are currently under research in spectroscopic studies; C 6 H 4 + , for example, was just recently shown to have a non-linear non-cyclic ground state structure [12].…”
Section: Mass Spectrometric Resultsmentioning
confidence: 99%
“…Rotationally resolved spectra, as previously obtained for carbon chain cations and carbon chain radicals using cavity ring down spectroscopy (see e.g., Refs. [12,13,22]) are within range and of particular astrophysical interest in view of the role carbon chain anions are expected to play in interstellar chemistry [23].…”
Section: Mass Spectrometric Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a nonlinear planar carbon chain radical C 6 H þ 4 , HACBCACBCACH@CH þ 2 (hereafter ''C 6 H þ 4 '' indicates this structural isomer, Fig. 1), was detected in a supersonic planar discharge by cavity ring down (CRD) spectroscopy in the 604 nm region [6]. The related C 4 H þ 4 and C 8 H þ 4 nonlinear carbon chains were also produced and detected in this plasma [7].…”
Section: Introductionmentioning
confidence: 83%
“…1) was recorded using high-resolution cw-CRD spectroscopy as part of this work. Additionally, an unassigned 585.3 nm absorption band, produced by a molecule having the same mass as C 6 H þ 4 , was observed in a 6 K neon-matrix [6]. To identify the carrier, this frequency region was scanned in the gas phase using cw-CRD spectroscopy, and a rotationally resolved band was observed at 581 nm.…”
Section: Introductionmentioning
confidence: 99%